To calculate the change in entropy S for the reaction, we need to find the difference between the total entropy of the products and the total entropy of the reactants.S = S products - S reactants First, let's find the total entropy of the reactants:2CH3OH l : 2 * 126.6 J/K = 253.2 J/K3O2 g : 3 * 205.0 J/K = 615.0 J/KTotal entropy of reactants = 253.2 J/K + 615.0 J/K = 868.2 J/KNow, let's find the total entropy of the products:2CO2 g : 2 * 213.6 J/K = 427.2 J/K4H2O l : 4 * 69.9 J/K = 279.6 J/KTotal entropy of products = 427.2 J/K + 279.6 J/K = 706.8 J/KFinally, let's calculate the change in entropy S :S = S products - S reactants = 706.8 J/K - 868.2 J/K = -161.4 J/KThe change in entropy for the reaction is -161.4 J/K.